Pandemic vs. Post-Pandemic Airport Operations: Hard Impact, Slow Recovery - Antonin Kazda; Benedikt Badanik; Francisco Serrano (Aerospace, 2022)
The elements of a new daily normal, airports need to face in post-pandemic operations, are massive flight delays, operational disruptions, and shortage of trained staff. The authors analysed the problems and reactions of airport human resources staff during the early stages of the COVID-19 pandemic and their approach to the management of human resources after the remission of the pandemic. Additionally, this paper describes problems of airports during the recovery phase and increases the understanding of specific problems airports are facing due to lack of qualified staff in their post-pandemic recovery period. Critical areas, in which airports underperform are ground handling services and security checks of passengers. Staff recruitment is not capable of providing enough workers to do the job. This leads to flight cancellations and delays or unsatisfied passengers during check-in and security. On top of this, ground-handling services remain unattractive for newcomers due to poor working conditions, such as low wages and 7 days a week shift work. ‘Cross-training’, allowing airports to have employees shadow colleagues from other airport teams, or ‘employee sharing’ (with other airports) could help in reducing problems, with unavailability of trained staff, especially at smaller airports.